The Impact of Shift Work-Related Circadian Rhythm Disruption on Inflammatory Biomarkers - Suyagh, Maysa; Alefishat, Eman; Abu Farha, Rana; Akour, Amal; Kasabri, Violet; Bulatova, Nailya (Jordan Journal of Pharmaceutical Sciences, 2018)
OBJECTIVE: This study aimed to examine the effect of circadian rhythm disruption in night-shift workers on systemicbiomarkers of inflammation. METHODS Demographic data, clinical parameters and data on working patterns of 126adult employees were documented. Serum levels of biomarkers were measured by enzymatic assay procedures.RESULTS: Night-shift workers had markedly lower anti-inflammatory IL-10 and cardioprotective adiponectin andMCP-1 compared to daytime workers. Night-shift workers’ MIF, LAR, TNF-α and TNF-α/IL-10 ratio weresignificantly higher than those in day shift workers. Spearman's correlation showed that MIF, TNF-α, LAR andTNF-α/IL-10 ratios were positively and significantly correlated with both the duration of the night shift and totalnumber of shifts (p < 0.05). Meanwhile, IL-10, adiponectin and MCP-1 were negatively and significantlycorrelated with both variables (p < 0.05).CONCLUSION: Night shift work may be closely associated with a higher propensity of cardiometabolic riskfactors clustering. Therefore, close monitoring of shift workers’ clinical status and lifestyle is warranted.